GE_GERICHTE P/6339/2014 vom 1. Dezember 2016 - GE Cour de justice (2016)
VIOLATION DES RÈGLES DE LA CIRCULATION; PEINE; ATTÉNUATION DE LA PEINE; ESPACE DE TEMPS; PRESCRIPTION | LCR.90.2; CP.47; CP.48.e